Duodenal Bezoar: A Rare Cause of Acute Pancreatitis - Henriette Ya Kissi Anzouan Kacou; Young-Il Kim (The Korean Journal of Helicobacter and Upper Gastrointestinal Research)
Gastrointestinal bezoars often occur as a complication of previous gastric surgery or in patients with altered gastrointestinal motility. Complications associated with gastrointestinal bezoars include perforation, peritonitis, protein-losing enteropathy, and acute appendicitis. Acute pancreatitis secondary to a duodenal bezoar is rare, and few studies have reported this complication. We report a case of acute pancreatitis and subsequent duodenal obstruction caused by a large duodenal phytobezoar.